Study results on estimation of non-specialized physical training university students in Hunan Province - Lihua Wang; Wei Shou Zhang (Physical Education of Students, 2013)
Highlights the results of the implementation of national standards of physical fitness assessment of students specialized universities Chinese province of Hunan. Discovered that the main negative factors that reduce the effectiveness in this area are the following: lack of unified management of the process of introducing national standards of physical fitness assessment of students; shortcomings in the quality and quantity of equipment for evaluation, the low level of mastery of the teaching staff of the methodology and insufficient use the results of monitoring the health of the students in the further education; misallocation of time for testing and evaluation in terms of physical health. Substantiates the importance of the rational organization of the assessment system, outlined the main directions of improving the effectiveness of the implementation of national standards of physical fitness of students.